Growth, Inequality, and Well-Being: Intertemporal and Global Comparisons - Carola Grün; Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2003)
We use several well-being measures that combine average income with a measure of inequality to undertake intertemporal and global comparisons of well-being. The conclusions emerging from the intertemporal analysis are that the impact of these measures on temporal trends in well-being is relatively small on average, but changing across the decades. In particular, it suggests that changes in well-being were understated in the 1960s and 1970s and overstated in the 1980s and 1990s. Our global analysis covering ca. 81 per cent of the world's population demonstrates that global well-being is at least 50 per cent smaller than world per capita income if the unequal income distribution is also factored in. Conversely, growth in world well-being has been larger than world income growth between 1970-1998. Since the inclusion of inequality has an important impact on well-being comparisons, it is of great importance to generate more consistent and intertemporally as well as internationally comparable data on inequality.
Keywords: I31; D63; 330; Lebensstandard; Einkommensverteilung; Sozialprodukt; Sozialer Indikator; Vergleich; Welt